Assistance for the Development of Furniture Products as Entrepreneurship Efforts in Pandanwangi Village Jombang - Ninik Sudarwati; Chalimah Chalimah (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
In recent years, both the government and the private sector have attempted to carry out several efforts and initiatives to promote various handicrafts and furniture in Indonesia, both through the media, cooperation programs and also exhibitions held in Indonesia. and abroad. But it is not effective enough to increase furniture production to a better level, especially among small industrial centers. Many small industrial centers, especially wood industrial centers scattered in several areas on the island of Java, have experienced suspended animation or have not increased both in terms of quality and quantity. Meanwhile, competition is getting tougher day by day, not only from within but also from abroad. Based on the results of research conducted in several wood centers on the island of Java, several factors were found as the cause, including: scarcity and quality of wood raw materials, limited mastery of wood technology, lack of innovation in design, promotion and marketing that was not integrated, and also lack of careful planning from the government in developing small industries. A good management strategy can develop businesses and provide solutions according to the conditions and needs of small industrial centers.